A guilty pleasure: The legal, social scientific and feminist verdict against rap - Khan, Ummni (Theoretical criminology, 2022)
This article draws on governance theory, critical theory and cultural criminology to interrogate how legal, social scientific and feminist discourses converge to construct rap music as a pressing social problem. While each discourse has its own preoccupations, ideologies and internal contestation, the overarching message is that rap music is a potential source of danger that conveys anti-social attitudes. Suspicion is sometimes also cast on musicians themselves. While I compare three overlapping fields, the ultimate purpose is to problematize the supposedly progressive approach to interpreting and mobilizing against songs deemed harmful. Significantly, I argue that much of the social science scholarship and feminist activism that addresses hip hop music perpetuates anti-Black stereotypes and dovetails with repressive state apparatuses. Among other things, social science and feminist criticism of rap hermeneutically support the use of rap lyrics as evidence of criminality—a distinctly non-progressive, racialized legal practice.